Penerapan Crime Prevention Through Enviromental Design (CPTED) Sebagai Upaya Pencegahan Pencurian Di Pusat Perbelanjaan Mtc Panam Pekanbaru - Riky Novarizal,; Nazzim Arradu, Al Fathir (Sisi Lain Realita, 2024)
This study aims to examine the implementation of Crime Prevention Through Environmental Design (CPTED) principles as a crime prevention strategy against theft at MTC Panam Shopping Center in Pekanbaru. CPTED is a crime prevention approach that utilizes environmental design and management, consisting of four main components: natural surveillance, access control, territorial reinforcement, and maintenance. This research uses a descriptive qualitative method with data collected through interviews with the head of security, security personnel, tenants, visitors, and local community members. The results show that MTC Panam has applied several CPTED principles, such as installing CCTV in strategic locations, restricting access to specific areas, deploying active security officers, and maintaining cleanliness and infrastructure. These efforts have contributed to a decrease in theft incidents and an increase in visitors' sense of safety. However, some limitations remain, such as a lack of security personnel during peak hours and uneven CCTV coverage. Therefore, greater collaboration among management, tenants, visitors, and the surrounding community is needed to create a safer and more secure shopping environment on an ongoing basis.